Research Trends in Public Budgeting for Half A Century - Andi Yudi Prayoga (Innovation Business Management and Accounting Journal, 2022)
The varying approaches and formats chosen by budget documents and the budgeting process from time to time can be explained by the complexity and diversity of budgeting functions, notably those of public budgets. Due to the vast amount of 982 articles by 1968 - August 2022 of research on public budgets in the Scopus database, it may be possible to determine research trends in this area through bibliometric analysis. Although the public budget publications' annual growth rate is small (7.88%), it demonstrates a positive increase yearly. The findings show the interest of various fields in researching public budgeting. It often investigates the connections between public budgeting and fiscal policy, public spending, participatory budgeting, and public debt from an economic point of view. Political science, sustainability, public administration, climate change, effectiveness, public services, performance, the public sector, and the European Union are all related to public budget studies. Researchers have expanded their research over the past three years by taking the Covid-19 epidemic into account as one of the catalysts for adjustments to public budgets in various nations.